2013
DOI: 10.3390/molecules180910146
|View full text |Cite
|
Sign up to set email alerts
|

Sinulariolide Induced Hepatocellular Carcinoma Apoptosis through Activation of Mitochondrial-Related Apoptotic and PERK/eIF2α/ATF4/CHOP Pathway

Abstract: Sinulariolide, an active compound isolated from the cultured soft coral Sinularia flexibilis, has potent anti-microbial and anti-tumorigenesis effects towards melanoma and bladder cancer cells. In this study, we investigated the effects of sinulariolide on hepatocellular carcinoma (HCC) cell growth and protein expression. Sinulariolide suppressed the proliferation and colony formation of HCC HA22T cells in a dose-dependent manner and induced both early and late apoptosis according to flow cytometry, Annexin V/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
0
40
1
Order By: Relevance
“…CHOP and ATF4 protein expressions are associated with ER stress (Cao et al, 2012;Chen et al, 2013). During ER stress, the levels of CHOP and ATF4 are elevated leading to apoptosis (Cao et al, 2012;Chen et al, 2013). However, the results show that oleuropein did not induce caspase-12 activation or increased CHOP and ATF4 protein levels in HepG2 cells.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…CHOP and ATF4 protein expressions are associated with ER stress (Cao et al, 2012;Chen et al, 2013). During ER stress, the levels of CHOP and ATF4 are elevated leading to apoptosis (Cao et al, 2012;Chen et al, 2013). However, the results show that oleuropein did not induce caspase-12 activation or increased CHOP and ATF4 protein levels in HepG2 cells.…”
Section: Discussioncontrasting
confidence: 61%
“…Data are mean ± SEM of three separate experiments. CHOP and ATF4 protein expressions are associated with ER stress (Cao et al, 2012;Chen et al, 2013). During ER stress, the levels of CHOP and ATF4 are elevated leading to apoptosis (Cao et al, 2012;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…9,29 Several crucial ER stress-related pathways, including the PERK/eIF2α/ATF4/CHOP, ATF6/ CHOP, and IRE1α/CHOP, have been revealed to be able to induce apoptosis in cancer cells. 9,10,29 Our Western blot results showed that treatment with pure HET results in increases in p-PERK, p-eIF2α, ATF4, IRE1α, and CHOP and a decrease in eIF2α, suggesting that HET is capable of eliciting apoptosis via several ER stress-associated pathways in bladder carcinoma cells. HA nanoparticles-aggregated HET at 0.1 and 0.2 µg/mL further enhanced these crucial ER stress apoptotic proteins compared with pure HET, implicating that HA nanoparticle aggregation may strengthen ER stress-related apoptosis induced by pure HET against bladder carcinoma cells.…”
mentioning
confidence: 67%
“…It has been found that several natural compounds from soft corals have cytotoxic and apoptosis-inducing effects against melanoma cells, hepatocellular carcinoma cells, and bladder cancer cells in our previous studies. 2,9,10 Heteronemin (HET) is a known sesterterpenoid extracted from the sponge Hippospongia sp. This natural marine compound was found to inhibit the enzyme protein farnesyltransferase and reduce the viability of leukemia cells, colon cancer cells, and breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation